Skills and competencies for sustainable food systems : case study of young market gardeners in Sweden - Lundgren, Lotten (SLU/Dept. of Plant Breeding (from 130101), 2020)
Global food systems are locked into a sociotechnical regime where actors are dependent on high external inputs and economies of scale, and systemic innovation is necessary to meet sustainability targets. Recent research into the development of education for fostering sustainability leaders, such as the Horizon 2020-project NextFood, have largely focused on mainstream agriculture, despite the importance of niches in driving systems change. The present thesis offers a perspective on one such niche, market gardening in Sweden.